2016
DOI: 10.1103/physrevlett.116.225001
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Magnetic Flux Annihilation Layer Formed by the Collision of Supersonic, Magnetized Plasma Flows

Abstract: We present experiments characterizing the detailed structure of a current layer, generated by the collision of two counterstreaming, supersonic and magnetized aluminum plasma flows. The antiparallel magnetic fields advected by the flows are found to be mutually annihilated inside the layer, giving rise to a bifurcated current structure-two narrow current sheets running along the outside surfaces of the layer. Measurements with Thomson scattering show a fast outflow of plasma along the layer and a high ion temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…Aluminium wires produced super-sonic (M S = 3.1), super-Alfvénic (M A = 2.2) inflows, which advected a B = 2T magnetic field at a flow velocity of V in = 50 km/s. 26 These inflows formed as the result of oblique shocks between the ablation streams from adjacent wires, which redirected the flows and formed a dense, collimated jet which propagated radially outwards from the gap between adjacent wires ( Fig. 3a).…”
Section: A Results From Experiments With Aluminium Wiresmentioning
confidence: 99%
“…Aluminium wires produced super-sonic (M S = 3.1), super-Alfvénic (M A = 2.2) inflows, which advected a B = 2T magnetic field at a flow velocity of V in = 50 km/s. 26 These inflows formed as the result of oblique shocks between the ablation streams from adjacent wires, which redirected the flows and formed a dense, collimated jet which propagated radially outwards from the gap between adjacent wires ( Fig. 3a).…”
Section: A Results From Experiments With Aluminium Wiresmentioning
confidence: 99%
“…As the interaction of the magnetized flows occurs over a relatively long timescale, with a continuous inflow of the magnetized plasma for many times the hydrodynamic timescale of the system (T ≫ L V flow ⁄ ), the power balance can be monitored as the reconnection process develops and the system evolves. The results have shown that there is a transfer of the kinetic and magnetic energy of the inflowing plasma to the kinetic and thermal energy inside the layer [25,[30][31][32].…”
Section: Magnetic Reconnection In Counter-streaming Magnetized Plasmamentioning
confidence: 98%
“…Magnetic reconnection is a complex and multifaceted process which is an active topic of research across space, astrophysics and plasma physics [28,29]. One of the most notable applications of the inverse wire array setup therefore has been to create a platform for studying this process in the laboratory [25,[30][31][32][33]. In these experiments two identical inverse wire arrays are fielded side-by-side on the MAGPIE generator, connected in parallel and in the same polarity to each receive a 50% share of the current supply.…”
Section: Magnetic Reconnection In Counter-streaming Magnetized Plasmamentioning
confidence: 99%
“…The pulsed-power-driven reconnection platform 12,13 uses two exploding wire arrays (Fig. 2a), In the experiments described in this paper, each array consisted of 16 carbon wires (Staedler Mars Micro Carbon B) with a diameter of 400 µm, evenly spaced around a circle with a 16 mm diameter.…”
Section: 21mentioning
confidence: 99%
“…In this paper we present a recently developed pulsedpower driven experimental platform, 12,13 which allows reconnection to be observed in a regime in which the magnetic, thermal and kinetic energies are in rough equipartition in the inflowing plasma. This platform converts initially solid wires into plasma using an intense pulse of electrical current, and then accelerates this plasma to high velocity.…”
Section: Introductionmentioning
confidence: 99%